ARRIVAL TIME OF ACUTE CORONARY SYNDROME (ACS) PATIENTS AT THE EMERGENCY DEPARTMENT BY MODE OF TRANSPORTATION: A CORRELATION STUDY - Harista, Dessy Rindiyanti; Rohman, Andrean Dwi Ainur; Amilia, Yunita; Nurseskasatmata, Satria Eureka (Universitas Kadiri, 2025)
In Acute Coronary Syndrome (ACS), the time elapsed between the onset of symptoms and the patient receiving treatment is an important determinant of survival and subsequent recovery. However, many patients do not receive treatment as quickly as recommended, largely due to substantial pre-hospital delays such as waiting to seek medical attention after the initial onset. Objective to determine the relationship between the mode of transportation used by patients and delays in their arrival at the Emergency Department (ED). This study used a cross-sectional design. The population in this study were SKA patients at Dr. Mohammad Zyn Sampang Regional General Hospital. The sampling technique used was simple random sampling, with a sample size of 35 people calculated using the Slovin formula. Based on data analysis and statistical tests, it was found that there was a relationship between the mode of transportation and the time of patient arrival at the ED. The arrival time of patients at the ED can be influenced by several factors, one of which is the mode of transportation used to go to the hospital. There is a need for education regarding the importance of arriving at the ED immediately for patients and families with Acute Coronary Syndrome